Pengaruh Keberadaan Dewan Komisaris Independen, Komite Audit, Dan Risk Management Disclosure Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Indeks LQ45 Di BEI) - I Made Restu Dwipayana; Ketut Tanti Kustina (Warmadewa Management and Business Journal (WMBJ), 2026)
This study aims to investigate the influence of independent commissioners, audit committees, and risk management disclosure on firm value in companies listed in the LQ45 Index on the Indonesia Stock Exchange (IDX) during 2022–2024. A quantitative approach was used, with secondary data obtained through documentation, and multiple linear regression employed for data analysis. A purposive sampling technique was applied, resulting in 30 companies that consistently appeared in the LQ45 index over the three-year period, producing 90 data observations. The findings reveal that all three variables significantly and positively affect firm value. Independent commissioners have a regression coefficient of 0.702 (p = 0.027), audit committees 0.741 (p = 0.000), and risk management disclosure 4.212 (p = 0.000), indicating that firms with stronger governance practices tend to be more highly valued in the market. These results imply that strengthening corporate governance through independent oversight, active auditing functions, and transparent risk disclosures is essential in boosting investor confidence and enhancing firm valuation.